The TREAT‐NMD Duchenne Muscular Dystrophy Registries: Conception, Design, and Utilization by Industry and Academia. Issue 11 (26th August 2013) - Bladen, Catherine L.; Rafferty, Karen; Straub, Volker; Monges, Soledad; Moresco, Angélica; Dawkins, Hugh; Roy, Anna; Chamova, Teodora; Guergueltcheva, Velina; Korngut, Lawrence; Campbell, Craig; Dai, Yi; et al.
Abstract : TREAT‐NMD is a worldwide network for neuromuscular diseases that provides an infrastructure to support the delivery of promising new therapies for patients. ABSTRACT: Duchenne muscular dystrophy (DMD) is an X‐linked genetic disease, caused by the absence of the dystrophin protein. Although many novel therapies are under development for DMD, there is currently no cure and affected individuals are often confined to a wheelchair by their teens and die in their twenties/thirties. DMD is a rare disease (prevalence <5/10, 000). Even the largest countries do not have enough affected patients to rigorously assess novel therapies, unravel genetic complexities, and determine patient outcomes. TREAT‐NMD is a worldwide network for neuromuscular diseases that provides an infrastructure to support the delivery of promising new therapies for patients. The harmonized implementation of national and ultimately global patient registries has been central to the success of TREAT‐NMD. For the DMD registries within TREAT‐NMD, individual countries have chosen to collect patient information in the form of standardized patient registries to increase the overall patient population on which clinical outcomes and new technologies can be assessed. The registries comprise more than 13, 500 patients from 31 different countries. Here, we describe how the TREAT‐NMD national patient registries for DMD were established. We look at their continued growth and assess how successful they have been at fostering collaboration between academia, patient organizations, and industry.